The Role of Majelis Ta'lim in Fostering Religious Attitudes: A Study at Majelis Ta'lim of Al-Qobul Mosque, Balikpapan - Ashari, Sukasah Ali; Yusuf, Iskandar (Journal of Educational Research and Practice, 2024)
Parents who are busy with work certainly cannot gain the necessary knowledge from formal educational institutions. Apart from age and time factors not being possible, they will also think about financial factors, most of them will choose to allocate it to meet their daily needs. In response to this, of course parents will look for other alternatives, one of which is taking part in a study at the Ta'lim Council. This research aims to determine the role of the Ta'lim Council in cultivating religious attitudes (Study at the Al-Qobul Balikpapan Mosque Ta'lim Council). Data collection techniques through observation, interviews and documentation studies then analyzing and making conclusions from the data that has been obtained. Based on the research results and discussion with reference to several theories and results of research carried out, the following conclusions can be drawn: 1) The ta'lim assembly plays an important role in cultivating the religious attitudes of the congregation who take part in assembly activities at the Al-Qobul Mosque, to complete the knowledge that can no longer be obtained from formal schools. 2) The activities of the ta'lim assembly broaden the insight and understanding of the congregation, especially regarding worship and matters related to it such as istinja, purification, ablution and so on. 3) The ta'lim assembly is a forum for resolving questions and problems experienced by its congregation, so that they can answer and resolve the problems they are experiencing clearly without any doubt or ambiguity.